Maksimalisasi Keuntungan Dengan Pendekatan Metode Simpleks Studi Kasus pada Pabrik Sendai X di Ciputat, Tangerang Selatan - Mela Rizqie Aulia; Dewaguna Negara Putra; Sari Murniati; Mustahiroh Mustahiroh; Debby Octavia; Yanti Budiasih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
The purpose of this study are to (1) to determine the number of allocation of those materials which is required for the maximum profit; and (2) to determine how many Rope and Rubber Sandals that must be sold to achieve the maximum profit by the industry. In order to determine the combination of inputs and maximum profits can be used linear programming with graphical and simplex method. The valuation result shows. The industry will take maximum profit from the Rope Sandals Rp. 26.436.000 if the company produces as much as 2203 pairs of sandals per month.